1969
DOI: 10.1128/aem.17.2.268-274.1969
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Persistence of Staphylococcus aureus on Fabrics

Abstract: The persistence of Staphylococcus aureus (Smith) on wool blanket, wool gabardine, cotton sheeting, cotton knit jersey, cotton terry cloth, and cotton wash-andwear fabrics was studied. The fabrics were exposed to bacterial populations by three methods: direct contact, aerosol, and a lyophilized mixture of bacteria and dust having a high content of textile fibers. The contaminated fabrics were held in 35 or 78%o relative humidities at 25 C. In general, the persistence time of S. aureus populations on fabrics hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…For staphylococci, our results are consistent with those of Wilkoff et al (17), who reported that one S. aureus isolate lived 1 week on cotton and 2 weeks on terry. In contrast, Scott and Bloomfield (12) showed S. aureus surviving only 4 to 24 h on cloth; however, their inocula were low (10 2 CFU).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For staphylococci, our results are consistent with those of Wilkoff et al (17), who reported that one S. aureus isolate lived 1 week on cotton and 2 weeks on terry. In contrast, Scott and Bloomfield (12) showed S. aureus surviving only 4 to 24 h on cloth; however, their inocula were low (10 2 CFU).…”
Section: Discussionsupporting
confidence: 92%
“…While most previous studies have tested survival of principally staphylococci using cotton as a representative fabric (2,12,17), the present study examined the survival of enterococci, including VRE, and staphylococci, on a number of different fabrics. Most of the bacteria tested in this study survived longer on polyester than on cotton.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vortexing was selected because it required fewer handling steps, thus reducing the chances of sample contamination and the risk of exposure of the laboratory personnel to the test bacterium. In previous studies (Wilkoff et al 1969), fabrics were eluted by cutting them into smaller pieces before macerating them in saline.…”
Section: Discussionmentioning
confidence: 99%
“…As might be predicted, the majority of organisms deposited on clothing, bedclothes and other items die rapidly; it has been shown by Wilkhoff et al (1969), however, that substantial populations of organisms such as Staph. aureus impregnated onto cotton and wool fabrics samples may remain viable and infective for considerable periods.…”
Section: (Iii) Clothing and Household Linenmentioning
confidence: 93%